FAKTOR-FAKTOR YANG MEMENGARUHI PROFIT DISTRIBUTION MANAGEMENT BANK UMUM SYARIAH DI INDONESIA PERIODE 2011-2016 - Adlina Sholfyta; Dian Filianti (Universitas Airlangga, 2018)
This research aims to find out the influence of financing to deposit ratio, deposit, and age of bank both partially or simultaneously to profit distribution management of islamic commercial bank in Indonesia. The sample are 8 islamic commercial banks in the period 2011-2016. This research uses quantitative approach by using secondary data in the form of financial statements of islamic commercial bank which listed on Bank Indonesia in year 2011- 2016. Regression result by using technique of panel data analysis with Eviews 6. The result showed that financing to deposit ratio and are partially giving significant influence to Profit Distribution Management. Meanwhile, age of bank have partially insignificant influence to Profit Distribution Management. imultaneously, financing to deposit ratio, deposit, and age of bank have significant influence to Profit Distribution Management with 27,82% value of coefficient determination, while the remaining 72,18% is influenced by other variables not included within this research. REFERENCESAnshori, Mucslich dan Sri Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Pusat Penerbitan dan Percetakan Unair.Antonio, Muhammad Syafi’i. 2001. Bank Syariah: Dari Teori ke Praktik. Jakarta: Gema Insani.Arikunto S, 2006. Prosedur Penelitian Suatu Pendekatan Praktik, Ed Revisi VI. Jakarta: PT Rineka Cipta.Departemen Agama RI. 2007. Al-Qur’an dan Terjemahnya. Bandung: Syaamil Cipta Media.Farook, Sayd, et all. 2012. Profit Distribution Management by Islamic Banks: An Empirical Investigation. The Quarterly Review of Economics and Finance, 52: 333-347.Fatwa Dewan Syarian Nasional MUI, Online, (https://dsnmui.or.id/produk/fatwa).Ghozali, Imam. 2011. Aplikasi Analisis Multivariate dengan Program IBM SPSS 19. Semarang: Universitas Diponegoro.Gujarati, Damodar. 2003. Basic Econometric. New York: The McGraw-Hill Companies,Inc. ————-. 2013. Ekonometrika Dasar Buku 2. New York: The McGraw- Hill Companies, Inc. Ismail. 2011. Perbankan Syariah. Jakarta: KencanaKarim, Adiwarman. 2012. Segmentasi Pasar Perbankan Syariah (Online), (http://www.adiwarmankarim.com/index.php?option=com_content&view=article&id=171%3Asegmentasi-pasar-perbankan-syariah&catid, diakses 1 April 2017)Kartika, Septiyana Bella. 2012. Analisis Faktor-Faktor yang Mempengaruhi Profit Distribution Management : Studi Empiris Bank Umum Syariah di Indonesia Periode 2009-2012. Jurnal Akuntansi Universitas Diponegoro Volume 1 Nomor 1 Tahun 2012. Muhammad. 2002. Manajemen Bank Syariah. Yogyakarta: Unit Penerbit dan Percetakan (UPP) AMPYKPN.————-. 2012. Teknik Perhitungan Bagi Hasil dan Pricing di Bank Syariah. Yogyakarta: UII Press.————-. 2015. Manajemen Dana Bank Syariah. Jakarta: PT RajaGrafindo PersadaRizaludin, Muhammad dkk. 2013. Analisis Pengaruh Variabel-variabel Determinan atas Profit Distribution Management terhadap para Nasabahnya pada Bank Syariah Indonesia, (Online), (http://lib.ui.ac.id/naskahringkas/2015-09/S45996-Muhammad%20Rizaludin, diakses 7 Desember 2017).Mulyo, Gagat Panggah dan Siti Mutmainah. 2013. Determinan Profit Distribution Management Bank Syariah di Indonesia Periode 2008-2011. Jurnal Ekonomi, Manajemen dan Akuntansi Islam (IMANESI) Volume 1 Nomor 1 Halaman 1-74. Nazir, Moh. 2014. Metode Penelitian. Bogor: Penerbit Ghalia IndonesiaOtoritas Jasa Keuangan. (2016). Statistik Perbankan Syariah. Jakarta: Otoritas Jasa Keuangan. Shihab, M.Quraish. 2002. Tafsir Al-Mishbah. Jakarta: Lentera Hati. Siagian, D. &. (2000). Metode Statistika untuk Bisnis dan Ekonomi. Jakarta: PT Gramedia Pustaka Utama. Soemitro, Andri. 2009. Bank dan Lembaga Keuangan Syariah. Jakarta: Kencana Prenada Media Group.Sudarsono, Heri. 2007. Bank & Lembaga Keuangan Syariah Deskripsi dan Ilustrasi. Yogyakarta: EKONISIA.Sugiyono. 2012. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Supomo, I. d. (2002). Metodologi Penelitian Bisnis untuk Akuntansi dan Manajemen. Yogyakarta: BPFE-Yogyakarta.Surat Edaran Bank Indonesia No.9/24/DPbS tanggal 30 Oktober 2007, Online, (http://www.bi.go.id/id/peraturan/perbankan/Documents/664a5003664b43aca6d788fd9d733229se_092407.pdf)Wafaretta, Vega., Rosidi & Aulia Fuad Rahman. The Impact of Banks Characteristics on Profit Distribution Management od Islamic Banks”. 3rd Global Conference on Business and Social Science-2015, GCBSS-2015, 16-17 December 2015, Kuala Lumpur, Malaysia.Widarjono, Agus. 2005. Ekonometrika : Teori dan Aplikasi untuk Ekonomi dan Bisnis. Yogyakarta: Ekonisia. ———–. 2010. Analisis Statistika Multivariat Terapan. Yogyakarta: UPP STIM YKPN———-. 2013. Ekonometrika:Pengantar dan Aplikasinya. Jakarta: Ekonosia.